(untitled) (Contemporary Journal of Social Science Review, 2026)
This study aims to explore how Howard Gardner’s five minds for the future—disciplined, synthesizing, creating, respectful, and ethical minds—can be reimagined to support inclusive education at the school level in the age of artificial intelligence. It examines how AI-based tools, digital learning environments, and learner-centered classroom practices can promote equity, accessibility, participation, and meaningful learning among diverse school students. A quantitative research design was used, and data were collected from a sample of 400 school students studying in Private and Public schools in the 9th class through a structured questionnaire. The collected data were analyzed using descriptive and inferential statistical techniques, including frequency, percentage, mean, and standard deviation, to interpret students’ responses and identify general trends. The findings suggest that inclusive education in the AI era requires more than access to digital tools; it requires teacher guidance, responsible technology use, cultural sensitivity, and equal learning opportunities. The study concludes that Gardner’s five minds provide a useful framework for building inclusive and future-ready school education where AI supports student diversity, creativity, and meaningful participation rather than replacing human values and teacher judgment.